Decision-making in opioid-dependent individuals using the Iowa Gambling Task - Areias, Graça (2016)
Decision-making impairments have been highlighted in opioid-dependent individuals using the Iowa Gambling Task (IGT). The objective of this study was to assess decision-making under uncertainty in opioid-dependent subjects. The sample included 64 abstinent opioid-dependent individuals under treatment and 48 control subjects. Group equivalence was analyzed considering age, gender and educational variables. In both groups, most subjects showed borderline performance, followed by disadvantageous performance and advantageous performance. Both groups showed a preference for low punishment frequency decks (B and D). In both groups, education and gender do not account for IGT performance, and learning differences in the IGT could be in part attributable to cognitive functions as assessed by the MoCA. Opioid- dependent individuals and the control group showed no significant differences in performance.